Desenvolvimento e avaliação do protótipo de semeadora-adubadora no sistema de camalhão - Nascimento, Elivânia Maria Sousa (2019)
The need to create specific machines that serve the small producer has been the way to improve the technological level of mechanization in small areas, mainly in the Brazil, where most of these producers still use the use of animal traction for agricultural operations. In this approach, the objective of this work was to develop and evaluate a prototype of a planter in ridge system. The project methodology for the development of the project consisted of four phases: informational, conceptual, preliminary and detailed design. To analyze the development needs of the product new was used as the basis the technological level family farm in the northeastern semiarid region. After the construction of the planter prototype, it was field tested to evaluate the process of formation of the ridge and seeding process, by means of the statistical control of the process, in order to verify the technical conformities and propose improvements that will meet the needs of the small producer. The study of quality through the statistic descriptive and process statistical control was stable, but the process capability was decentralized, requiring adjustments to suit the quality standards. The longitudinal distribution of seeds for normal spacing is above 70% in all parameters. The process for the quality of seed spacing and seed depth kept stable can thus be considered as only natural causes that occur in the process. The prototype used as a satisfactory result does not refer to the longitudinal distribution of seeds, but it is necessary to make improvements so that it reaches the depth necessary for the formation of the ridges and the opening of the furrow. The use of the FMEA method was efficient to identify critical quality indicators and how to cause it.